Islamic Social Finance and Poverty Alleviation - Furqon, Ainul; Nurhayat, Nurhayat; Mukhid, Mukhid (Economics Studies and Banking Journal (DEMAND), 2024)
Islamic social financing, including zakat, waqf, and infaq, has attracted attention as a potential tool in poverty alleviation, especially in Muslim-majority countries. This research aims to analyze the effectiveness of Islamic social financing in reducing poverty in Muslim-majority countries compared to non-Muslim countries. The research method used was PRISMA to systematically review the literature from relevant articles. The research results show that Islamic social financing has significant potential in reducing poverty and income inequality. The implication of this research is the importance of improving the management and distribution of zakat, waqf and infaq funds to maximize their impact on social and economic welfare.